Phase-sensitive breast CT with monochromatic beam towards the clinical trial. (September 2016) - Longo, R.; Arfelli, F.; Bellazzini, R.; Brez, A.; Brun, F.; Cova, M.A.; Delogu, P.; Di Lillo, F.; Dreossi, D.; Fedon, C.; Golosio, B.; Mettivier, G.; et al.
Abstract : Introduction: The first clinical trial of phase-contrast mammography with monochromatic beam was performed at Elettra, the Italian Synchrotron Radiation facility. A lower Mean Glandular Dose (MGD) and a higher specificity were achieved compared to the digital mammography for the patient cohort (more than 70). Purpose: The SYRMA-CT project (SYnchrotron Radiation for MAmmography – Computed Tomography) aims to perform the first clinical trial of phase-sensitive breast CT with monochromatic beam. High image quality and low dose are expected according to the results of the first mammography trial. Materials and methods: A large area CdTe single photon counting detector (PIXIRAD-8) is used. Phase-retrieval algorithm are applied, thus exploiting propagation based phase-contrast imaging (PPCI). The dose system of the beamline has been calibrated to match the energy requirement up to 40 keV. Due to the peculiar irradiation modality, ad hoc Monte Carlo simulations and experimental measurements were performed for dose evaluation. Results: Images of surgical samples included in large test objects (up to 12 cm diameter) were acquired at 38 keV in clinical compatible dose conditions (MGD ∼5 mGy). Phase-retrieval pre-processing was applied improving the CNR of the high-resolution images with (120 μm) 3 voxel size. Conclusion: The upgrade of the mammographic facility of the Elettra laboratory towards a new clinical trial is going on. Image quality and dose assessment indicate its feasibility with monochromatic beam. This clinical trial will allow the evaluation of PPCI breast CT in optimal conditions and will give indication for the translation to the hospital of phase-sensitive techniques. Disclosure: Nothing to declare.